Direct and Indirect Effects of Income Inequality On Economic Growth Through Political Economy - Aslan, Goksu (Journal of Income Distribution®, 2019)
In addition to its direct effects, income inequality may affect economic growth indirectly through various transmission channels. Negative effects may arise from a political economy, socio-political instability, and credit market imperfections. In other words, inequality may have indirect effects on economic growth through these transmission channels. In this article, the focus is on testing the impact of income inequality through the political economy channel, using several types of taxes as the proxy for redistributive pressure. In order to test the possible effects through these channels, income inequality, taxation, and related interaction terms are added into the growth model. The results show that there is a significant negative interaction between income inequality and tax channels. This interaction is also justified with the tax index calculated by the PCA. Marginal effects of the related tax channels are interpreted for different levels of income inequality.